2004
DOI: 10.1158/0008-5472.can-03-2818
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-Dependent Kinase Inhibition by the KLF6 Tumor Suppressor Protein through Interaction with Cyclin D1

Abstract: Kruppel-like factor 6 (KLF6) is a tumor suppressor gene inactivated in prostate and colon cancers, as well as in astrocytic gliomas. Here, we establish that KLF6 mediates growth inhibition through an interaction with cyclin D1, leading to reduced phosphorylation of the retinoblastoma protein (Rb) at Ser 795 . Furthermore, introduction of KLF6 disrupts cyclin D1-cyclin-dependent kinase (cdk) 4 complexes and forces the redistribution of p21Cip/Kip onto cdk2, which promotes G 1 cell cycle arrest. Our data suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 140 publications
(121 citation statements)
references
References 44 publications
4
117
0
Order By: Relevance
“…Overexpression of cyclins has also been observed frequently in HCC cases, 25 and we recently demonstrated that KLF6 can bind and inactivate cyclin D1 and converge with the Rb pathway. 26 KLF6 may also up-regulate the insulin-like growth factor 1 receptor, 27 the loss of which could contribute to HCC. 28 Finally, apoptotic activity of KLF6 has been reported in lung cancer cell lines, 13 and down-regulation of this apoptotic potential could enable emergence of neoplastic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of cyclins has also been observed frequently in HCC cases, 25 and we recently demonstrated that KLF6 can bind and inactivate cyclin D1 and converge with the Rb pathway. 26 KLF6 may also up-regulate the insulin-like growth factor 1 receptor, 27 the loss of which could contribute to HCC. 28 Finally, apoptotic activity of KLF6 has been reported in lung cancer cell lines, 13 and down-regulation of this apoptotic potential could enable emergence of neoplastic cells.…”
Section: Discussionmentioning
confidence: 99%
“…cdk4 Immunoprecipitation Kinase Assay-This was performed essentially as described previously (22). Cells were lysed in 50 mM Hepes (pH 7.5), 150 mM NaCl, 1 mM EDTA, 0.1% Nonidet P-40 detergent with 10% glycerol, 100 M phenylmethylsulfonyl fluoride, 10 g/ml aprotinin, 10 g/ml leupeptin, 100 M sodium vanadate, and 20 g/ml TLCK (1 h, 4°C), centrifuged, and 700 g of lysate was immunoprecipitated with mAb anti-cdk4, mAb anti-cyclin D1, or mouse IgG (overnight, 4°C).…”
Section: Kip2mentioning
confidence: 99%
“…The Klf6 transcription factor acts to regulate transcription of Ccnd1 (Benzeno et al 2004). The Klf6 gene was suggested to be overexpressed in the PO × BW class.…”
Section: Perturbation Of Cell Cycle Regulatory Genes In the F 1 Hybridsmentioning
confidence: 99%